Pengembangan Keterampilan Kewirausahaan Digital Mahasiswa UM-Tapsel melalui Pelatihan Intensif di Era Revolusi Industri 4.0 - Suleman, Abdul Rahman; Siregar, Muhammad Noor Hasan (Jurnal Pengabdian kepada Masyarakat Radisi, 2024)
The "Digital Entrepreneurship Training" program was designed to enhance digital entrepreneurship literacy and entrepreneurial readiness among students of the Economic Education program at Universitas Muhammadiyah Tapanuli Selatan (UMTS). The training, conducted over three days, involved 30 participants and utilized interactive sessions, case studies, hands-on practice, group discussions, and business simulations. Results showed an average increase in pre-test and post-test scores of 25.6%, reflecting significant improvements in participants' knowledge and skills. Project evaluations indicated that most participants successfully developed comprehensive and realistic digital business plans. Feedback from participants also showed high satisfaction with the content, facilitators, and training methods. However, some participants required additional mentoring to refine their business plans. Overall, the program effectively achieved its goals and can serve as a model for similar future training programs, preparing young generations to face challenges and seize opportunities in the digital era.